Preservasi konten fisik dan digital pada perpustakaan perguruan tinggi - Marleni, Marleni; Rodin, Rhoni; Martina, Anna (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2022)
Background. The development of information technology encourages university libraries to apply it in library activities. The purpose of this study is to analyze how physical and digital content is preserved in university libraries.Methodology. This study uses a qualitative approach with descriptive analysis. Data collection techniques are carried out by literature review / literature study related to the preservation of physical and digital content in college libraries. Data analysis was performed by criticizing, comparing, summarizing, and gathering (synthesizing) some literatures. Thus, the method used in this paper is literature study with an emphasis on peeling, summarizing and collecting literature, then analyzing the data that has been collected.Results and discussion. In university libraries, efforts to preserve the value of information so that information can be used for a relatively longer period of time and avoid damage to digital or electronic collections requires strategies to be carried out in carrying out physical and digital content preservation activities. Strategies that can be carried out by higher education libraries in preserving physical and digital content are 1) Technology Preservation; 2) Refreshing or Updating (Refreshing); 3) Migration and Reformating (Migration and Reformating); 4) Emulation (Emulation); 5) Digital Archeology; and 6) Digital to analogConclusions. College libraries have carried out physical and digital content preservation activities in the current era. Although there are still some things that need to be improved and improved in the future.